MAMLAKATIMIZDA INKLYUZIV TA’LIMNING HOZIRGI HOLATI VA RIVOJLANISH TENDENSIYALARI - Pirniyazova, G.N. (SCIENCE and SOCIETY, 2025)
In this article, the current state of inclusive education in our country, the adopted regulatory and legal framework, the conditions created for the participants of inclusive education, and the indicators of children with special educational needs included in inclusive education until now, are analyzed and theoretical information is given.